Active control of suddenly expanded flow from under expanded nozzles - Khan, Sher Afghan; Rathakrishnan, E. (Walter de Gruyter, 2004)
This paper presents an experimental investigation to study the effectiveness of micro-jets to control base pressure in suddenly expanded axi-symmetric ducts. Four micro-jets of 1 mm orifice diameter located at 900 interval along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed as active controls. The Mach numbers of the suddenly expanded flows were 1.25, 1.3, 1.48, 1.6, 1.8, and 2.0. The jets were expanded suddenly into an axi-symmetric tube with cross-sectional area 2.56, 3.24, 4.84, and 6.25 times that of nozzle exit diameter. The length-to-diameter ratio of the sudden expansion tube was varied from 10 to 1. The jets at all Mach number were operated at an under expansion level of Pe/Pa = 1.5. The wall pressure distribution in the suddenly enlarged duct was also measured. It is found that the micro-jets can serve as active controllers for base pressure. Also, the wall pressure distribution is not adversely influenced by the micro-jets. From the present investigation it is evident that for a given Mach number and nozzle pressure ratio one can identify the enlargement length to diameter ratio which will result in maximum increase/decrease of base pressure.